1998
DOI: 10.1002/(sici)1098-2396(199812)30:4<424::aid-syn9>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Group I mGluRs modulate calcium currents in rat GP: Functional implications

Abstract: The modulation of voltage-dependent calcium currents strongly affects the firing pattern of central neurons. Changes in the intrinsic firing properties of mammalian globus pallidus cells (external pallidus in humans) are indicated as underlying the development of movement disorders. Pallidal neurons receive an excitatory input from the subthalamus, supposed to activate both ionotropic and metabotropic glutamate receptors. Since the activation of glutamate metabotropic receptors in rodent basal ganglia affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
0
14
1
Order By: Relevance
“…The inhibition of P/Q-type Ca 2ϩ channels by group 1 mGluRs has been reported in several neuronal cells as well as heterologously expressing cells (30,31,55). This investigation has indicated that mGluR1a inhibits Ca v 2.1 Ca 2ϩ channels in both ligand-dependent and ligand-independent manners, which are mediated by the mechanisms of the membrane-delimited G i /G o coupling and the physical coupling between the two proteins, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The inhibition of P/Q-type Ca 2ϩ channels by group 1 mGluRs has been reported in several neuronal cells as well as heterologously expressing cells (30,31,55). This investigation has indicated that mGluR1a inhibits Ca v 2.1 Ca 2ϩ channels in both ligand-dependent and ligand-independent manners, which are mediated by the mechanisms of the membrane-delimited G i /G o coupling and the physical coupling between the two proteins, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…The coincident rise in [Ca 2ϩ ] i is important for integrating synaptic inputs to PNs (2,28,29). In contrast, the stimulation of group 1 mGluRs has been shown to inhibit P/Q-type Ca 2ϩ channels in cortical and globus pallidus neurons (30,31). However, neither temporally regulated mechanisms of mGluR1-mediated P/Qtype Ca 2ϩ channel modulation nor the physical interaction between mGluR1 and P/Q-type Ca 2ϩ channels have been addressed yet.…”
mentioning
confidence: 99%
“…An additional observation in the present study is that mGluR1 regulates the activity of pallidal neurons in normal awake monkeys. No in vivo experiments have so far been conducted to examine the contribution of mGluR1 to the behavior of pallidal neurons, nor have data from in vitro experiments extensively been available (Stefani et al ., 1998; Poisik et al ., 2003). Our extracellular unit recordings have revealed that DHPG (an agonist of group I mGluRs) significantly increases the spontaneous firing rate of pallidal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…I L , I K (Baranauskas et al, 1999;Hernandez-Pineda et al, 1999), I Na , I C a (Surmeier et al, 1994;Stefani et al, 1998), and I AHP are modeled with the same formulas and equations given above for the STN cells, whereas the low-threshold calcium current takes a simpler form: (Baranauskas et al, 1999). These parameters were selected to match the data for spontaneous firing patterns, rebound response to offset of hyperpolarization, spike frequency adaptation, and frequency -intensity curves obtained from the study of GPe cells in slices (K ita and K itai, 1991;Nambu and L linãs, 1994;Cooper and Stanford, 2000).…”
Section: Methodsmentioning
confidence: 99%